Report on 36 Schemes on Government of India Vol. 1 (Mussoorie LBSNAA, 2023)
This book comprises the analysis of 36 Central government Schemes/Projects, forming multi sub group, each sub group dealing with one schemes in detail. the schemes broadly covered the key aspects of the sustainable development goals, such as agriculture and rural development, socio-economic inclusion, social infrastructure and social security, urban goverenance, culture and climate smart infrastructure etc.
Keywords: Report on 36 Schemes of Government of India